Antimony Selenide Nanorods Decorated on Reduced Graphene Oxide with Excellent Electrochemical Properties for Li-Ion Batteries. Issue 13 (1st January 2017) - Wang, Xia; Wang, Hong; Li, Qiang; Li, Hongsen; Xu, Jie; Zhao, Guoxia; Li, Hongliang; Guo, Peizhi; Li, Shandong; Sun, Yang-kook
Abstract : A promising anode material for lithium-ion batteries (LIBs) consisting of Sb2 Se3 nanorods and reduced graphene oxide (rGO) sheets has been prepared by an effective solvothermal approach. The synergetic effect between Sb2 Se3 nanorods and rGO matrix provides not only high conductivity paths and strong electron contact interface, but also alleviates the volume change of Sb2 Se3 nanorods, resulting in excellent lithium-storage performance. When tested as an anode material for LIBs, a high capacity of 868.30 mAh g −1 can be retained after 100 cycles at 200 mA g −1 . Even at 2000 mA g −1, a satisfactory capacity of 430.40 mAh g −1 after long 550 cycles can be delivered. Ex situ X-ray diffraction study suggests that the Sb2 Se3 /rGO composite follows the combined Li + intercalation, conversion reaction and alloying reaction mechanism. These features suggest the Sb2 Se3 /rGO composite a viable choice for application as an anode material in high-performance LIBs.